Short-term low-intensity blood flow restricted interval training improves both aerobic fitness and muscle strength - Oliveira, Mariana Fernandes Mendes de [UNESP]; Caputo, Fabrizio; Corvino, Rogério Bulhões; Denadai, Benedito Sérgio [UNESP] (Wiley-Blackwell, 2015)
The present study aimed to analyze and compare the effects of four different interval-training protocols on aerobic fitness and muscle strength. Thirty-seven subjects (23.8 ± 4 years; 171.7 ± 9.5 cm; 70 ± 11 kg) were assigned to one of four groups: low-intensity interval training with (BFR, n = 10) or without (LOW, n = 7) blood flow restriction, high-intensity interval training (HIT, n = 10), and combined HIT and BFR (BFR + HIT, n = 10, every session performed 50% as BFR and 50% as HIT). Before and after 4 weeks training (3 days a week), the maximal oxygen uptake (VO2max ), maximal power output (Pmax ), onset blood lactate accumulation (OBLA), and muscle strength were measured for all subjects. All training groups were able to improve OBLA (BFR, 16%; HIT, 25%; HIT + BFR, 22%; LOW, 6%), with no difference between groups. However, VO2max and Pmax improved only for BFR (6%, 12%), HIT (9%, 15%) and HIT + BFR (6%, 11%), with no difference between groups. Muscle strength gains were only observed after BFR training (11%). This study demonstrates the advantage of short-term low-intensity interval BFR training as the single mode of training able to simultaneously improve aerobic fitness and muscular strength.
Keywords: Short-term interval training; Vo2max; Blood flow restriction; Cycling; High-intensity exercise; Isometric knee extension torque